Text-Based Plagiarism in Scientific Writing: What Chinese Supervisors Think About Copying and How to Reduce it in Students’ Writing - Li, Yongyan (Springer Netherlands, 2012)
Text-based plagiarism, or textual copying, typically in the form of replicating or patchwriting sentences in a row from sources, seems to be an issue of growing concern among scientific journal editors. Editors have emphasized that senior authors (typically supervisors of science students) should take the responsibility for educating novices against text-based plagiarism. To address a research gap in the literature as to how scientist supervisors perceive the issue of textual copying and what they do in educating their students, this paper reports an interview study with 14 supervisors at a research-oriented Chinese university. The study throws light on the potentiality of senior authors mentoring novices in English as an Additional Language (EAL) contexts and has implications for the efforts that can be made in the wider scientific community to support scientists in writing against text-based plagiarism.